PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS III SDN 3 BUNGATAN SITUBONDO - Yanti Fatjariah; Agus Wijaksono; Andi Wapa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Bakti Indonesia, 2023)
This research is research that aims to determine the increase in learning Indonesian when applying the Role Playing learning method in class III SDN 3 Bungatan. The implementation of this study was planned in two cycles. The first cycle of the implementation of learning jarimatika in 3 meetings. And the second cycle of the implementation of learning jarimatika in 3 meetings as well. The final results of cycle 1 are compared with the results of cycle 2 to determine the level of increase. The level of results is as follows: in cycle I the lowest score was 50 and the highest score was 95, with an average score of 67.9 and a completeness percentage of 52.9%. Whereas in cycle II the highest score was 100 and the lowest score was 60, with an average score of 81.2 and a completeness score of 88.2%.